Pemanfaatan Sampah Limbah Rumah Tangga Sebagai Pupuk Organik Cair Terhadap Pertumbuhan Bibit Kakao (Theobroma Cacao L) - Yuanita (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2017)
The quantity of garbage accumulated in the cities from time to time is increasing that it has become difficult to manage as it is associated with not only hygiene but also disposal issues. Thus it is necessary to conduct a research to discover the right method in managing household waste into liquied organic fertilizer. Not only the fertilizer will reduce the quantity of garbage, it also can be applied to cacao plants. The goal of this research was to analyze the impact of liquid organic fertilizer made out of household waste on the growth of cocoa seeds. Completely randomized design with four treatments and ten replication were used. Treatment 1 (P1) wasthe control; treatment 2 (P2) was 15 cc liquid organic fertilizer/liter water; treatment 3 (P3) was 25 cc liquid organic fertilizer/liter water; and treatment 4 (P4) was 35 cc liquid organic fertilizer/liter water. The results indicate that the application of liquid organic fertilizer was not significant on all parameter tested (the number of leaves, height of plant and diameter of cocoa seed). Out of all parameters tested, P3 showed the highest score while P0 the lowest.